KEMAMPUAN REPRESENTASI MATEMATIS DALAM MATERI FUNGSI DENGAN PENDEKATAN OPEN ENDED PADA SISWA KELAS VIII MTs SIRAJUL ULUM PONTIANAK - Hartono Hartono; Muhammad Firdaus; Sipriyanti Sipriyanti (Universitas Muhammadiyah Kotabumi, 2019)
The purpose of this study was to determine the ability of mathematical representation through an open-ended approach to functional material in class VIII MTs. Sirajul Ulum Pontianak. The research method used was the experimental method with Quasi experimental research and the design used in this study was posttest-only control design. The results obtained were (1) the average ability of students' mathematical representation after being taught with an open-ended approach was 72 with the criteria classified as good; (2) The average mathematical representation ability of students is 57 with criteria classified as sufficient; and (3) The ability of mathematical representations given to the treatment of open-ended approaches is better than students given the treatment of conventional learning models, this can be seen from the average results and has been proven using inferential statistics. Every student in the control class or experiment experiences problems on each indicator, which is what distinguishes the average.